Without consent : a landmark trial and the decades-long struggle to make spousal rape a crime - Weinman, Sarah (Ecco, an imprint of HarperCollins Publishers, 2025)
"From Sarah Weinman, author of Scoundrel and The Real Lolita, comes an eye-opening story about the first major spousal rape trial in America and urgent questions about women's rights that would reverberate for decades. In 1978, Greta Rideout was the first woman in United States history to accuse her husband of rape, at a time when the idea of "marital rape" seemed ludicrous to many Americans and was a crime in only four states. After a quick and conservative trial acquitted John Rideout and a defense lawyer lambasted that "maybe rape is the risk of being married," Greta was ridiculed and scorned from public life, while John went on to be a repeat offender. Thrust into the national spotlight, Greta and her story would become a national sensation, a symbol of a country's unrelenting and targeted hate toward women and a court system designed to fail them at every turn. A now little-remembered trial deserving of close, wide, and lasting attention, Sarah Weinman turns her signature intelligence and journalistic rigor to the enduring impact of this case. Oregon v. Rideout directly inspired feminist activists, who fought state by state for marital rape laws, a battle that was not won in all fifty until as recently as 1993. Mixing archival research and new reporting involving Greta, those who successfully pressed charges against John in later years, as well as the activists battling the courts in parallel, Without Consent embodies vociferous debates about gender, sexuality, and power, while highlighting the damaging and inherent misogyny of American culture then and still now"-- Provided by publisher.